Menumbuhkan Budaya Bisnis Masyarakat: Kajian Pembiayaan Kredit Usaha Produktif di Kabupaten Kudus - Teguh Hadi Prayitno; Alimuddin Rizal; Musthofa Musthofa (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
This research, which was conducted in Kudus Regency, Central Java, photographed the condition of Micro, Small and Medium Enterprises (MSMEs) using a sample of 250 respondents. It evaluates the productive business credit program (KUP) that is being channeled to already running MSMEs. The KUP, which was initiated by the Kudus Regency Government together with banking and insurance institutions as credit guarantee institutions, has proven to be able to bridge the problems faced by MSMEs related to the difficulty of accessing capital. As a result, MSMEs increase their incomes, employment, and reduce bad loans in banks. The business culture of the community in Kudus Regency is an ancestral heritage existing long before the independence of the Republic of Indonesia which continues to thrive due to the increasing quality of MSMEs. The credit distribution with the KUP pattern has proven to be able to awaken the business culture of the community.